The position of ambiguity Given the role of words and meanings in contracts in the five denominations - seyedmehdi nezhadhahshemi; Ali bahraminezhad; Mohamadreza Emam 2 (مطالعات تطبیقی فقه و اصول مذاهب, 2019)
From the viewpoint of some popular jurisprudents (al-Maliki and Han'ablah), if one considers the al, The principle in contracts is the terms of the contract, not its words or its root word what is attributed to the Ima'im and Shafi'i is the validity of the contract and the principles. Not in its intentions and meanings, but in fact, in the Imamiyyah jurisdiction, on the one hand, it is one of the prestigious terms in the contract, and on the other hand, the rule of al-Aqud is a subsidiary of Laqsud, which holds the heart of the covenant. It means that the word is literal in the same sense, and in order to be bold it wants to use the word, whether it is sex or news that testifies Rejection, if there is no intention, there will be no contracts in worship or transactions, and the rhetoric alone will not be in the Imamiyyah jurisprudence according to the rationale and the principle of corruption in the contract, from various Shafi'is, indicating various beliefs. The literal sufficiency alone is the examination of the citation of Torah in contractual terms which is apparently inaccurate and in the context of the intentions and meanings of the validity of the contract, and it has led us to consider what position the Torah in the plural between literal and meaning will have in the contract. If there was a conflict, how would this conflict, and how to respond to it, be avoided? Law, and as permitted by half-truth be blocked